Large-Scale Arrayed Analysis of Protein Degradation Reveals Cellular Targets for HIV-1 Vpu - Prashant Jain (Cell Reports, 2018)
Summary: Accessory proteins of lentiviruses, such as HIV-1, target cellular restriction factors to enhance viral replication. Systematic analyses of proteins that are targeted for degradation by HIV-1 accessory proteins may provide a better understanding of viral immune evasion strategies. Here, we describe a high-throughput platform developed to study cellular protein stability in a highly parallelized matrix format. We used this approach to identify cellular targets of the HIV-1 accessory protein Vpu through arrayed coexpression with 433 interferon-stimulated genes, followed by differential fluorescent labeling and automated image analysis. Among the previously unreported Vpu targets identified by this approach, we find that the E2 ligase mediating ISG15 conjugation, UBE2L6, and the transmembrane protein PLP2 are targeted by Vpu during HIV-1 infection to facilitate late-stage replication. This study provides a framework for the systematic and high-throughput evaluation of protein stability and establishes a more comprehensive portrait of cellular Vpu targets. : Retroviruses use their accessory proteins to evade immune detection and enhance viral replication. Jain et al. developed a high-throughput–high-content imaging platform to study protein stability and degradation. This method was then applied to reveal cellular targets of the HIV-1 accessory factor Vpu. Keywords: Vpu, HIV-1, high-content imaging, protein degradation, interferon-stimulated genes, antiviral, ISGylation, immune evasion